Weak-strong uniqueness for the Navier–Stokes–Poisson equations. (May 2020) - He, Lianhua; Tan, Zhong
Abstract: This paper is devoted to study the weak-strong uniqueness property of compressible Navier–Stokes–Poisson system. By means of relative entropy method, we prove the result that the weak solution coincides with the strong solution, emanating from the same initial data, as long as the latter exists.